2004
DOI: 10.1071/fp04046
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of lateral rooting to phosphorus acquisition efficiency in maize (Zea mays) seedlings

Abstract: Low soil phosphorus availability is a primary constraint for plant growth in many terrestrial ecosystems. Lateral root initiation and elongation may play an important role in the uptake of immobile nutrients, such as phosphorus, by increasing soil exploration and phosphorus solubilisation. The overall objective of this study was to assess the value of lateral rooting for phosphorus acquisition through assessment of the 'benefit' of lateral rooting for phosphorus uptake and the 'cost' of lateral roots in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(173 citation statements)
references
References 40 publications
11
161
0
1
Order By: Relevance
“…The advantages of this have been demonstrated, for example, in bean (Phaseolus vulgaris) where genotypes with highly branched, actively growing root systems have been shown to be more P efficient than genotypes lacking such root traits (Lynch and Brown 2001). This has also been confirmed in brassicas (Hammond et al 2009) and demonstrated for production of lateral roots (Zhu and Lynch 2004). Leaf growth depression under phosphorus deficiency is also well documented (Chiera et al 2002, Assuero et al 2004, Kavanová et al 2006.…”
Section: Resultsmentioning
confidence: 49%
“…The advantages of this have been demonstrated, for example, in bean (Phaseolus vulgaris) where genotypes with highly branched, actively growing root systems have been shown to be more P efficient than genotypes lacking such root traits (Lynch and Brown 2001). This has also been confirmed in brassicas (Hammond et al 2009) and demonstrated for production of lateral roots (Zhu and Lynch 2004). Leaf growth depression under phosphorus deficiency is also well documented (Chiera et al 2002, Assuero et al 2004, Kavanová et al 2006.…”
Section: Resultsmentioning
confidence: 49%
“…In young plants with few axial roots, lateral branching may increase exploration of soil domains not reached by axial roots. This may account for the observation that increased lateral rooting among young maize RILs under phosphorus stress was associated with substantially greater phosphorus accumulation and growth (Zhu and Lynch, 2004). Lateral branching is under complex genetic control in maize, where 15 relatively small effect QTL have been identified (Zhu et al, 2005a).…”
Section: Lateral Branchingmentioning
confidence: 93%
“…In a study of the root morphology of temperate pasture species, a reduction in root diameter, root mass density, and an increase in specific root length were observed under P stress (Hill et al, 2006). Reduced lateral root diameter also has been described under low P in water hyacinth (Eichhornia crassipes) and maize (Zea mays; Xie and Yu, 2003;Zhu and Lynch, 2004). Nevertheless, observations of reductions in root diameter under P stress have not been made within root classes, and published reductions in root diameter of the entire root system may be the product of a greater proportion of higher order lateral roots rather than the effects of altered secondary growth.…”
mentioning
confidence: 99%